Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s11172-009-0335-5
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of tellurium tetrachloride with acetylene

Abstract: No data on the reaction of tellurium tetrachloride with acetylene are available, however, it is known that tellurium tetrachloride reacts with substituted acetyl enes. 1-7 Reactions of tellurium tetrachloride with phenyl acetylene, diphenylacetylene, and arylalkynes are known to proceed as the syn addition resulting in Z configured products exclusively. 1-6 This was confirmed by X ray dif fraction data. 4 Reactions of organyltellurium trichlorides with alkynes also proceed as the syn addition resulting in Z or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 10 publications
(2 reference statements)
0
6
0
1
Order By: Relevance
“…[10][11][12][13][14][15] We are making a systematic study of the reactions of tellurium tetrahalides with unsaturated compounds. [16][17][18][19][20][21][22][23][24][25] Recently we have found that methoxytelluration can be accomplished by the reaction of tellurium tetrabromide with 1-hexene in methanol. 17 The reaction proceeded with high regioselectivity to afford Markovnikov's products, tribromo-(2-methoxyhexyl)-λ 4 -tellane.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] We are making a systematic study of the reactions of tellurium tetrahalides with unsaturated compounds. [16][17][18][19][20][21][22][23][24][25] Recently we have found that methoxytelluration can be accomplished by the reaction of tellurium tetrabromide with 1-hexene in methanol. 17 The reaction proceeded with high regioselectivity to afford Markovnikov's products, tribromo-(2-methoxyhexyl)-λ 4 -tellane.…”
Section: Introductionmentioning
confidence: 99%
“…Наше дослідження присвячено синтезу нових функціоналізованих ненасичених конденсованих похідних хіназолін-4-ону та дослідження регіохімії процесу електрофільної гетероциклізації під дією телур тетрахлориду. Вибір такого електрофільного реагенту зумовлено тим, що в останні роки дедалі активніше розвивається органічний синтез халькогеновмісних сполук, зокрема, телуровмісних [7][8][9][10][11], які проявляють широкий спектр біологічної активності [12][13][14]. Тому синтез телуровмісних сполук на основі хіназолін-4-ону є важливим завданням з огляду на їх перспективні біологічні властивості.…”
unclassified
“…The stereoselective synthesis of ditellurides containing 2-halovinyl group is an important synthetic problem in the chemistry of organotellurium compounds. As a rule, the preparation of these compounds is based on the addition of tellurium tetrachloride to alkynes [3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…Earlier, we have first performed the reaction of tellurium tetrachloride with acetylene, which occurs stereoselectively as the anti-addition and results depending on the conditions of the reaction in Е-(2chlorovinyl)tellurium trichloride or Е,Е-bis(2-chlorovinyl)telluriumdichloride [3][4][5]. The reduction of Е-(2chlorovinyl)tellurium trichloride by sodium pyrosulfite affords Е,Е-bis(2-chlorovinyl)ditelluride [3][4][5], which was used for introduction of the Е-2-chlorovinyltellurium group in organic compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation